Wastewater-based surveillance for severe acute respiratory syndrome coronavirus 2 variants in Gwangju, Republic of Korea - Lee, Chaeyoung; Park, Jungwook; No, Jin Sun; Kim, Jongpil; Seo, Jungmi; Kim, Dongju; Kim, Il-Hwan; Kim, Eun-Jin (Frontiers in Microbiology, 2025)
The coronavirus disease pandemic has underscored the importance of surveillance systems for timely response to public health threats. Genomic surveillance of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is essential for tracking the emergence and dissemination of variants of the virus. However, as clinical surveillance is conducted primarily among symptomatic individuals and their contacts, the ability to detect asymptomatic infections and undiagnosed cases is limited. Accordingly, in this study, we evaluated the utility of wastewater-based surveillance as a complementary approach to traditional clinical monitoring methods. From epidemiological weeks 1–21 in 2024, samples were collected from three wastewater treatment plants in the Gwangju region of South Korea. Quantification of SARS-CoV-2 RNA and whole-genome sequencing revealed that temporal changes in the viral concentration closely mirrored the confirmed case counts. Comparative analysis was conducted of the Illumina MiSeq and NextSeq platforms, revealing that the NextSeq platform exhibited relatively higher sensitivity in sequencing depth and genome coverage. Analysis of wastewater-derived sequences further revealed that the sublineage diversity in the samples closely resembled that of contemporaneous clinical isolates. Our findings highlight the utility of wastewater-based surveillance as an effective adjunct to conventional systems, as the method enhances the capacity to monitor SARS-CoV-2 transmission dynamics and variant emergence within the community.